2007
DOI: 10.1111/j.1365-2354.2006.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

The reported views and experiences of cancer service users from minority ethnic groups: a critical review of the literature

Abstract: There is growing evidence of inequalities in access to high-quality cancer services between minority and majority ethnic groups. However, little research has been carried out from the perspective of users from minority ethnic groups themselves. This paper reports a review of the British literature exploring the views and experiences of cancer service users from minority ethnic groups. We reviewed 25 qualitative studies that reported the experiences of people from minority ethnic groups. The studies highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…Some argue that there is a lack of 'cultural transferability' in existing Western palliative service models which may make them unacceptable to some non-western people (Gunaratnam, 2001). In addition to this, language barriers Jack et al, 2001) may be a barrier to access to reliable information about end-of-life care services, such as hospice and cancer care facilities (Elkan et al, 2007;Randhawa and Owens, 2004). This may significantly impede awareness and uptake of palliative care services (Gaffin et al, 1995;Jones, 2005;NCHSPCS, 2003;PRIAE, 2006;Smaje and Field, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Some argue that there is a lack of 'cultural transferability' in existing Western palliative service models which may make them unacceptable to some non-western people (Gunaratnam, 2001). In addition to this, language barriers Jack et al, 2001) may be a barrier to access to reliable information about end-of-life care services, such as hospice and cancer care facilities (Elkan et al, 2007;Randhawa and Owens, 2004). This may significantly impede awareness and uptake of palliative care services (Gaffin et al, 1995;Jones, 2005;NCHSPCS, 2003;PRIAE, 2006;Smaje and Field, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Perceptions of cultural insensitivity and language problems echo barriers expressed in breast and cervical screening research, indicating a need for greater engagement on this issue among health practitioners and staff and possible change at the practice level. 21,22 African-Caribbean participants also highlighted the reluctance of some men in their community to have the test because they regarded it as a challenge to their masculinity. However, a recent study examining screening uptake figures indicated no significant difference between AfricanCaribbean men and women and research has suggested this reluctance is not exclusive to African-Caribbean men.…”
Section: Message Dissemination and Screening Location † General Practmentioning
confidence: 99%
“…Caucasian cancer populations dominate studies of unmet supportive needs while for patients from other ethnic groups' needs prevalence and patterns remain indistinct [4]. Ethnic minorities ubiquitously experience disproportionate negative disparities in cancer care [22,23] amplifying unmet need [24]. Identifying the basis for these disparities is critical for improving care [22].…”
mentioning
confidence: 99%